The Role of GRIT on Subjective Well-Being in Adolescents - zahra Salsabila; Sisca Eunique Gunawan; Rafif Verlantyno; Thalisa Kania Nugraha; Erik Wijaya (PT Publikasiku Academic Solution, 2024)
The prevalence of mental health issues among adolescents has become a significant concern, with subjective well-being playing a crucial role in their overall happiness. Understanding the factors that contribute to subjective well-being is essential, particularly in educational settings. This study aims to examine the impact of GRIT on the subjective well-being of adolescents, hypothesizing that higher levels of GRIT will be associated with improved subjective well-being. 300 adolescents participated in this study, with data collected through online questionnaires administered from October 20 to November 10, 2024. The analysis was conducted using linear regression to explore the relationship between GRIT and subjective well-being. The analysis revealed a significant positive correlation between GRIT and subjective well-being, with a coefficient of determination (R²) of 0.223. This indicates that GRIT accounts for 22.3% of the variance in subjective well-being, with a significant p-value of 0.040. The findings suggest that higher levels of GRIT positively influence the subjective well-being of adolescents. This underscores the importance of fostering GRIT in educational contexts to enhance students' overall happiness and life satisfaction.